How to do everything with Microsoft Office Access 2007 - Andersen, Virginia (New York : McGraw-Hill, 2007)
Maximize the powerful features of the latest release of today's most popular desktop database program. How to Do Everything with Microsoft Office Access 2007 shows you how to create and customize an efficient, multi-user database, retrieve, interpret, and share your data, secure your information, and much more. Designed to help you get things done quickly and easily, this user-friendly guide is your all-access pass to Access 2007.
pt. I. Get Started -- Get Acquainted with Access 2007 -- Create a Database -- Create and Modify Tables -- Relate Tables -- Enter and Edit Data -- pt. II. Retrieve and Present Information -- Sort, Filter, and Print Records -- Extract Information with Queries -- Create Advanced Queries -- Understand Form Report Design Basics -- Create Custom Forms and Subforms -- Create and Customize Reports and Subreports -- Create Charts and Graphs -- pt. III. Improve the Access 2007 Workplace -- Customize the Workplace Speed Up Your Database -- Automate with Macros -- Customize the User Interface -- Customize the Navigation Pane and Create Switchboards -- pt. IV. Exchange Data with Others -- Exchange Database Objects and Text -- Exchange Data with Outside Sources -- Share with Multiple Users -- Secure a Database -- Appendix. Convert to Access 2007.
Includes index.
Keywords: Microsoft Access; Microsoft Access; Database management -- Computer programs; Database Management Systems